FimX, a Multidomain Protein Connecting Environmental Signals to Twitching Motility in Pseudomonas aeruginosa - Huang, Bixing (American Society for Microbiology, 2003)
Twitching motility is a form of surface translocation mediated by the extension, tethering, and retraction of type IV pili. Three independent Tn5-B21 mutations of Pseudomonas aeruginosa with reduced twitching motility were identified in a new locus which encodes a predicted protein of unknown function annotated PA4959 in the P. aeruginosa genome sequence. Complementation of these mutants with the wild-type PA4959 gene, which we designated fimX, restored normal twitching motility. fimX mutants were found to express normal levels of pilin and remained sensitive to pilus-specific bacteriophages, but they exhibited very low levels of surface pili, suggesting that normal pilus function was impaired. The fimX gene product has a molecular weight of 76,000 and contains four predicted domains that are commonly found in signal transduction proteins: a putative response regulator (CheY-like) domain, a PAS-PAC domain (commonly involved in environmental sensing), and DUF1 (or GGDEF) and DUF2 (or EAL) domains, which are thought to be involved in cyclic di-GMP metabolism. Red fluorescent protein fusion experiments showed that FimX is located at one pole of the cell via sequences adjacent to its CheY-like domain. Twitching motility in fimX mutants was found to respond relatively normally to a range of environmental factors but could not be stimulated by tryptone and mucin. These data suggest that fimX is involved in the regulation of twitching motility in response to environmental cues.